The Possibility of Collective Action in Tozkoparan against Urban Regeneration Project from the Perspective of Political Process Theory - Duman, Betul; Coskun, Ismail (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2016)
This study focuses on the Tozkoparan neighborhood and investigates the collective action and mobilization dynamics against urban regeneration project. Neighborhood is a social housing area which is developed as an owner occupation site. Tozkoparan is also distinguished by its high level of neighborhood belonging, large public spaces, and low building density. Although the regeneration efforts are not being at the stage of physical destruction, we have found out that both the demands on capitalizing exchange value and the need to renovate small and old dwellings are effective in residents' attitude. In this context, Neighborhood association formed against top-down project management can become an agent of mobilization only if it pursues politics of compensation on behalf of residents. Furthermore, although the local government's repressive strategy leaves little room for collective action, unfair management of the process as well as producing results like loss of rights and displacement, can generate new political opportunities.
Keywords: Urban regeneration; Collective action and mobilization; Political opportunities and threats; Local government's repressive strategies; Tozkoparan social housing area; MOVEMENTS; PROTEST; CITIES; TURKEY; Sociology